2021
DOI: 10.1021/acs.energyfuels.1c01386
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Storage Stability for Biocrude Derived from Hydrothermal Liquefaction of Microalgae

Abstract: The instability of hydrothermal liquefaction (HTL) biocrude has impeded the broader utilization of fuel and chemical feedstock. In this paper, we investigated the storage stability of biocrude produced from HTL of microalgae. The biocrude showed good stability in phase homogeneity and water content, whereas the viscosity and average molecular weight increased by 48.4 and 41.9%, respectively, after storing for 12 months. Thermogravimetric analysis (TGA) and asphaltene content analysis indicated more high-boilin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…First of all, the wastewater treatment cost would be reduced if the organic load is converted into a valuable product, with the remaining one being recycled; secondly, it compensates the environmental cost of the fossil H 2 ; moreover, if a green H 2 source is proposed (i.e., electrolysis powered by renewable energy), it would currently have higher costs. Furthermore, partial deoxygenation of the BC would be beneficial for the storage properties and avoid the increase of the viscosity 49,50 . In fact, several research groups showed that partially upgraded BCs could be processed together with fossil‐derived fuels in conventional refineries 51 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, the wastewater treatment cost would be reduced if the organic load is converted into a valuable product, with the remaining one being recycled; secondly, it compensates the environmental cost of the fossil H 2 ; moreover, if a green H 2 source is proposed (i.e., electrolysis powered by renewable energy), it would currently have higher costs. Furthermore, partial deoxygenation of the BC would be beneficial for the storage properties and avoid the increase of the viscosity 49,50 . In fact, several research groups showed that partially upgraded BCs could be processed together with fossil‐derived fuels in conventional refineries 51 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, partial deoxygenation of the BC would be beneficial for the storage properties and avoid the increase of the viscosity. 49,50 In fact, several research groups showed that partially upgraded BCs could be processed together with fossilderived fuels in conventional refineries. 51 Other technologies investigated for the production of H 2 via the processing of HTL-AP are, among the others, supercritical water gasification (SCWG), also called hydrothermal gasification (HTG) and electrochemical oxidation (EO).…”
Section: Toward Htl and Apr Integrationmentioning
confidence: 99%
“…11,12 The HTL process is advantageous in saving on the feedstock drying cost, requiring a lower heating energy input, and reducing the requirement for special facilities, compared with other thermochemical conversion processes (pyrolysis, gasication, and carbonization). 13,14 Moreover, the HTL operating conditions provide a sub/supercritical water environment to kill pathogens and passivate the heavy metals in MSS. 6 Hence, the HTL conversion of MSS could be a promising method for the disposal and recycling of municipal sludge waste.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to petroleum crudes, biocrudes are more compositionally complex, more reactive, and more susceptible to aging . The compositional complexity of biocrudes creates challenges for their refining or coprocessing with petroleum feedstocks. Biocrudes also tend to be quite corrosive to metallic surfaces (especially at elevated temperatures), which adversely impacts their transportation, storage, and processing. The corrosivity of biocrudes has been attributed to various protic oxygen containing molecular components, including alcohols, phenolics, carboxylic acids, and water. Such Brønsted acids are also known to catalytically accelerate dehydrative condensation and oligomerization/polymerization reactions to form larger molecules and polymeric structures with reduced solubility, which lead to biocrude instability .…”
Section: Introductionmentioning
confidence: 99%
“…The compositional complexity of biocrudes creates challenges for their refining or coprocessing with petroleum feedstocks. Biocrudes also tend to be quite corrosive to metallic surfaces (especially at elevated temperatures), which adversely impacts their transportation, storage, and processing. The corrosivity of biocrudes has been attributed to various protic oxygen containing molecular components, including alcohols, phenolics, carboxylic acids, and water. Such Brønsted acids are also known to catalytically accelerate dehydrative condensation and oligomerization/polymerization reactions to form larger molecules and polymeric structures with reduced solubility, which lead to biocrude instability . In addition, condensation reactions may occur during biocrude aging, causing precipitation of deposits associated with clogging and fouling of process equipment. An improved understanding of relationships between biocrude’s corrosivity or instability and its native hydroxyl group containing populations is needed to inform production best practices and aid further integration of biocrude into the energy industry.…”
Section: Introductionmentioning
confidence: 99%